An Ecoregion-Based Approach to Protecting Half the Terrestrial Realm - DINERSTEIN, ERIC; OLSON, DAVID; JOSHI, ANUP; VYNNE, CARLY; BURGESS, NEIL D.; WIKRAMANAYAKE, ERIC; HAHN, NATHAN; PALMINTERI, SUZANNE; HEDAO, PRASHANT; NOSS, REED; HANSEN, MATT; LOCKE, HARVEY; et al. (Bioscience, 2017)
We assess progress toward the protection of 50% of the terrestrial biosphere to address the species-extinction crisis and conserve a global ecological heritage for future generations. Using a map of Earth’s 846 terrestrial ecoregions, we show that 98 ecoregions (12%) exceed Half Protected; 313 ecoregions (37%) fall short of Half Protected but have sufficient unaltered habitat remaining to reach the target; and 207 ecoregions (24%) are in peril, where an average of only 4% of natural habitat remains. We propose a Global Deal for Nature—a companion to the Paris Climate Deal—to promote increased habitat protection and restoration, national- and ecoregion-scale conservation strategies, and the empowerment of indigenous peoples to protect their sovereign lands. The goal of such an accord would be to protect half the terrestrial 2050 to halt the extinction crisis while sustaining human livelihoods.